Income associations with cigarette purchasing behaviors and quit attempts among people experiencing homelessness. (August 2019) - Vijayaraghavan, Maya; Neisler, Julie; Wrighting, Quentaxia; Reitzel, Lorraine R.; Hébert, Emily T.; Rash, Carla J.; Kendzor, Darla E.; Businelle, Michael S.
Abstract: Introduction: Cigarette purchasing behavior may reflect quitting intentions. Little is known about how income could modify the association between cigarette purchasing behaviors and quit attempts among smokers experiencing homelessness. Methods: Homeless, current smokers completed a questionnaire on the amount spent weekly on cigarettes (≤$20/week versus >$20/week), source of cigarettes (store versus other source), quantity of cigarettes purchased (<pack versus ≥pack), and past-year quit attempts. The association of participant income and these cigarette purchasing behaviors were examined. The relationship between cigarette purchasing behaviors and quit attempts was also examined and monthly income (none versus any) was explored as a potential moderator of this relationship. Results: Of the 472 currently smoking individuals, 55% reported spending >$20/week on cigarettes, 83% reported purchasing cigarettes from a store, and 86% reported purchasing ≥pack during their last purchase. Those who reported an income spent a third of their monthly income on cigarettes, and were more likely to spend >$20/week on cigarettes. The amount spent weekly on cigarettes and the source of cigarettes was not associated with quit attempts, nor did income moderate these relationships. Persons without an income who bought a pack or more of cigarettes made fewer quit attempts (β = −0.4, 95% CI −0.7, −0.2), whereas the association between quantity of cigarettes purchased and quit attempts was not significant for those with an income (β = −0.2, 95% CI −0.4, 0.1). Conclusions: Current smokers experiencing homelessness and who are without an income may find it particularly challenging to engage in attempts to quit smoking. Smoking cessation interventions that highlight relief of financial hardship as a potential benefit of successfully quitting smoking may be useful among this population. Highlights: Homeless adults spend a third of their monthly income on tobacco. Having an income is associated with more cigarette spending among homeless smokers. Those without an income who purchase a larger quantity of cigarettes are less likely to initiate quit attempts. Smoking cessation interventions may have an important role in relieving financial hardship in this vulnerable population.